Saúde indígena no território do Baixo Amazonas: o (não)acesso dos Hixkaryanas da aldeia Kassawá aos serviços de saúde nos municípios de Nhamundá e Parintins - Wotete, Francy (Brasil, 2025)
This research is part of the debate on the indigenous issue and its relationship with Social Services. In particular, it deals with the particularity of indigenous health in the rural context of Lower Amazonas from a single perspective, which is that of the indigenous people themselves in their access to public health services. Thus, the central objective is to analyze the Hixkaryana people's (non)access to health policy in the municipalities of Nhamundá and Parintins, territory of Lower Amazonas, taking as a reference the perspective of indigenous leaders from the Kassawá village. This is an innovative study in the area of training in Social Service at the Institute of Social Sciences, Education and Animal Science (ICSEZ) at the Federal University of Amazonas (UFAM), as it seeks to bring the reality of indigenous people Hixkaryana from rural Amazonian areas in their relations with public health policy. It is an exploratory research of a qualitative nature, based on an effort to approach the dialectical method, being sequenced in two moments: 1) bibliographic review, 2) field study. In the latter, the participants were indigenous leaders and/or residents of Aldeia Kassawá who, during the period of the field study, were in the city of Nhamundá. As instruments, a script with open and closed questions, semi-structured interview, field diary and systematic observation were used; and the data analysis process was based on the content analysis technique. The results observe a double journey, if on the one hand there were advances in legislation and health care; on the other hand, the entire difference principle was not taken into account in this process.